Replication of short selling in Islamic Finance: potential structures and issues - Hasan, Aznan; Khan, Sarfaraz Dawar; Bachok, Rabiatul Adawiyah; Redzuan, Nur Harena (2013)
This paper discusses the practice of short selling and its application in Islamic capital markets. Short selling has always been a subject of debate and criticism not only in the sphere of Islamic finance but also the conventional. Though short selling may serve as a tool for providing liquidity and better price discovery to the traders, it is argued that use of short selling has caused an adverse effect on financial markets. This was quite evident during the financial crisis of 2007-08 and European sovereign debt crisis which led regulators in countries like United States, France, Belgium, Italy, Spain, Greece and Turkey had imposed temporary ban on short selling on certain sectors of the markets. In short selling, the trader sells stocks at certain agreed market price and would later buys those stocks at the price lessor than the sold value and make profit on the exercise. The seller does not really own the stocks that are sold in short selling (or he might just borrow in when selling). This is one of the reasons that makes the practice of short selling in Islamic capital markets is objectionable. In addition, there are other factors that make short selling non-shari’ah compliant. These factors are: The practice short selling is perceived to involve heavy speculation that mostly verges gambling. Secondly, the existence of interest (if the stocks are bowrrowed) makes short selling unacceptable from Shariah perspective. Lastly, it contravenes maslahah (public interest), that is, it may results in market manipulation and could potentially lead to the instability of the market. The main objective of this paper is to examine and discuss the structure of short selling and to find suitable alternative from Shariah perspective for making it shariah compliant. Six potential Shari’ah compliant models are discussed in this paper which can be used for structuring shari’ah compliant short selling. These shari’ah contracts are: Urbun, Wa’ad, Wakalah, Mudharabah, bai’ salam and Musharakah.